2006
DOI: 10.4049/jimmunol.176.3.1553
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Naive CD4 T Cells to Polarizing Cytokine Determines the Ratio of Th1 and Th2 Cell Differentiation

Abstract: The intrinsic features of naive CD4 T cells that affect their ability to respond to polarizing signals for Th cell differentiation are not well understood. In this study, we show that naive CD4 T cells from mice transgenic for the Hlx gene expressed lower levels of IL-4Rα. The down-regulation of IL-4Rα diminished IL-4 signaling and the Th2 response and enhanced the Th1 response under suboptimal polarizing conditions. In nontransgenic CD4 T cells, blocking IL-4Rα with Abs had the same effect in an Ab dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
(51 reference statements)
2
27
0
Order By: Relevance
“…The dichotomy of type 1 and type 2 cells stands as a central paradigm that provides the framework to understand the nature of an immune response that is either beneficial or detrimental to the host (34,52). Our data showed that uptake of a larger number of R. conorii correlated with a higher level of IL-12p40 production in B6 BMDCs compared to those of C3H counterparts (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The dichotomy of type 1 and type 2 cells stands as a central paradigm that provides the framework to understand the nature of an immune response that is either beneficial or detrimental to the host (34,52). Our data showed that uptake of a larger number of R. conorii correlated with a higher level of IL-12p40 production in B6 BMDCs compared to those of C3H counterparts (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…All animal studies were performed in compliance to rules stipulated in the policies of the University of Rochester Committee on Animal Research. As previously described (18,37), for Th1 and Th2 cell differentiation, CD4 T cells were stimulated with OVA 223-239 peptide (0.5 g/ml) or ConA (Sigma-Aldrich) (2.5 g/ml) plus T cell-deleted spleen cells as APC and 50 U/ml human IL-2 (Roche). For Th1 differentiation, the cultures were supplemented with IL-12 (Biogen) (5 ng/ml) and anti-IL-4 Abs (11B11) (BD Pharmingen) (1 g/ml), whereas for Th2 differentiation, the cultures were supplemented with IL-4 (BD Pharmingen) (10 ng/ml), anti-IFN-␥ (XMG1.2) and anti-IL-12 Abs (BD Pharmingen) (1 g/ml).…”
Section: Do1110camentioning
confidence: 99%
“…Because IL-4 is required for normal T H 2 differentiation, Hlx deficiency results in impaired production of T H 2 cytokines, and this phenotype can be reversed by ectopic retroviral expression of IL-4R␣. 34 Apart from promoting T H 2 differentiation, IL-4 is a potent inhibitor of IFN-␥ production by T cells. 35 Therefore, by decreasing the responsiveness of a CD4 ϩ T cell to IL-4 during early T H 2 polarization, Hlx may indirectly promote the production of IFN-␥ by this lymphocyte population.…”
Section: Discussionmentioning
confidence: 99%